Authorea
DOI: 10.22541/au.158559989.96244770
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Infections in Wild Boars (Sus scrofa) from Southern Switzerland: Diagnostic Improvements, Epidemiological Situation and Zoonotic Potential

Abstract: The occurrence of mycobacterial infections in different hosts and their implication as obligate or opportunistic pathogens remain mainly unclear. In addition to the well-known pathogenic members of the Mycobacterium tuberculosis -complex (MTBC), over 180 nontuberculous mycobacteria (NTM) species have been described. Although the large majority of the NTM are assumed to be non-pathogenic to most individuals, an increasing trend in NTM infections has been observed over the last decades. The reasons of such augme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 79 publications
(104 reference statements)
0
12
2
Order By: Relevance
“…Based on this observation, it is unlikely that new MAH lineage was introduced from these regions. It is reported that MAH is isolated from wild boars in Europe (39), however, MAH is not isolated from wild animals in the same area of this study (40). Epidemiological information from farms harboring infected pigs revealed that the source of the new MAH lineage was likely introduced by pig movement.…”
Section: Discussioncontrasting
confidence: 56%
“…Based on this observation, it is unlikely that new MAH lineage was introduced from these regions. It is reported that MAH is isolated from wild boars in Europe (39), however, MAH is not isolated from wild animals in the same area of this study (40). Epidemiological information from farms harboring infected pigs revealed that the source of the new MAH lineage was likely introduced by pig movement.…”
Section: Discussioncontrasting
confidence: 56%
“…The specimen was decontaminated and processed as described before. 11,12 Direct Ziehl-Neelsen staining of the decontaminated material revealed acid-fast bacilli (Figure 3). Three days after inoculation of liquid mycobacterial media (BBL MGIT, Becton Dickinson, Switzerland) supplemented with PANTA (polymyxin B, amphotericin B, nalidixic acid, trimethoprim, azlocillin) antibiotic mixture, and incubation at 30 • C, growth was detected.…”
Section: Investigationsmentioning
confidence: 99%
“…A swab sample from the purulent skin lesion was submitted for mycobacterial culture. The specimen was decontaminated and processed as described before 11,12 . Direct Ziehl‐Neelsen staining of the decontaminated material revealed acid‐fast bacilli (Figure 3).…”
Section: Investigationsmentioning
confidence: 99%
See 2 more Smart Citations